Development of reduced fat minced meats using inulin and bovine plasma proteins as fat replacers - Rodriguez Furlán, Laura Teresa (2014)
Thiswork dealswith the effect of the addition of inulin and bovine plasma proteins as fat replacers, on the quality of minced meat. The proteins are obtained by ultrafiltration and freeze-drying. The following determinations were carried out: chemical composition, sensorial analysis (color, flavor, taste and consistency), emulsion stability and instrumental texture analysis of samples. The resulting formulationswere comparedwith full-fatminced meat, as control. The results showed an increase of protein contents after fat replacement,while a fat reduction of 20?35% produced light products enriched with proteins and inulin as the functional ingredient. No change was observed in color, flavor, or taste among the samples. However, the sensory analysis showed that the combination of plasma protein (2.5%w/w) and inulin (2%w/w) had the best acceptabilitywith respect to consistency, and had a lower fat drain from the emulsion. Texture profile analysis revealed that this formulation assimilated thecontrol texture properties, being that this result is required for adequate consumer acceptance.